Postoperative hypoalbuminemia as a risk factor for surgical site infection after oral cancer surgery. (25th March 2014) - Lee, J‐I; Kwon, M; Roh, J‐L; Choi, JW; Choi, S‐H; Nam, SY; Kim, SY
<x xml:space="preserve">Abstract</x> Objectives Postoperative surgical site infection (SSI) is a frequent postoperative complication in patients with oral cancer and significantly affects patient recovery and medical expenses. The aim of this study was to examine the predictors of SSI in patients undergoing major surgery for oral or oropharyngeal squamous cell carcinoma (OSCC) and to determine the relationship between perioperative albumin and the development of SSI. Subjects and methods In 337 consecutive patients who underwent clean‐contaminated surgery for OSCC, serum albumin, glucose, and hemoglobin levels were perioperatively measured. Differences between the groups were examined using Fisher's exact test, Mann–Whitney U‐test, and multiple logistic regression analysis. Results Surgical site infection was detected in 88 (26.1%) patients with median time to development of 10 (2–25) days. Multiple logistic regression analysis showed that only postoperative serum albumin < 2.5 g dl−1 was an independent variable predictive of SSI (P = 0.003). The duration of hospital stay was negatively correlated with postoperative albumin (R2 = –0.302, P < 0.001). Conclusion Early postoperative hypoalbuminemia <2.5 g dl−1 is an independent risk factor for the development of SSI in patients undergoing oral cancer surgery. Clinicians should be aware of the implications of postoperative hypoalbuminemia and consider more intensive postoperative care in these patients.